Exploring students entrepreneurial mindset. Insights to foster entrepreneurship in engineering education - João, Isabel (2018)
Higher education graduates have a huge potential forinnovative processes and sustainable economic development. The higher education institutions must play an important role in engaging students for entrepreneurial careers, enhancing their skills in entrepreneurship. Students capable of identifying opportunities and turning ideas into business, who have good communication and leadership skills as well as strong technical competencies are likely to be highly valued in the marketplace. This paper presents the results of a survey to investigate students’ entrepreneurial mindset. The main concern is to understand the interest of the students in entrepreneurship and reasons to start or not start a business, the engineering students’ perceptions of their entrepreneurial related abilities, as well as their perception about the extent by which entrepreneurship is addressed in their engineering programs. The students were selected among two engineering master courses in a Portuguese Engineering School of a Polytechnic Institute. The curricular unit of entrepreneurship is part of the curriculum in one of the master course, while in the other course the students do not have such subject in their study program. The data were collected to investigate differences within and across engineering students who are and who are not participating in entrepreneurship courses as well as diferences concerning some demographic characteristics.